OVERCOMING OF THE MUTENESS: THE PUBLIC PERFORMANCES OF THE MACEDONIAN WOMEN IN XIX CENTURY (Philological Studies, 2019)
The noted speeches of Macedonian teachers in the nineteenth century indicate that their consciousness has gone beyond the traditional patriarchal way of thinking. They demanded the right to education and emancipation in society. Their views, paraphrased by correspondents, show the degree of development of womеn's thought in Macedonia at the end of the XIX and the beginning of the XX century. Having into consideration the situation with women's education and female voicelessness just about ten years before the end of the century, we can conclude that great progress has been made in the suppression of illiteracy and voicelessness. The public performances of the Macedonian teachers were also of great importance for this.
Keywords: public performances, speeches, teachers, women's education, woman's emancipation, Evgenija Janchuleva